The resilience of the ruins: towards a critique of digital humanitarianism. Issue 3 (1st September 2016) - Duffield, Mark
Abstract: With humanitarian disaster management as its background, this article takes a critical look at some recent changes in the nature of security governance; especially, the withdrawal from face-to-face engagement on the ground in favour of techniques of distant sensing and remote management. Despite the optimism and affirmatory policy claims surrounding the adoption of data informatics to recoup distance, the paper argues that such hubris is blind to its disabling governmental effects. Global connectivity enables resilience to come of age. In what this paper calls the resilience of the ruins, data informatics operationalises experimental systems of welfare abandonment under conditions of pervasive security surveillance. Using examples drawn from cash-transfer programmes and current Google and Facebook plans to connect difficult to reach populations in the global South, it is concluded that, harnessed to the neoliberal project, new technology locks-in the negativities of actually existing capitalism.